SENI FOTOGRAFI SEBAGAI EKSPRESI BARU BUDAYA - Malik Fathur Fathurrohman; Maya Purnama Sari (Specta: Journal of Photography, Arts, and Media, 2021)
Art of Photography as a New Expression in Culture. Photography at the beginning of its history had a function as a painting aid, with a prototype called the ‘camera obscura’ which then contin- ued to develop along with the emergence of new discoveries about lenses, cameras, light-sensitive chemicals that developed from glass plates into films and photo paper. Now, photography not only has a function as a medium to perpetuate an event, but also functions as a medium for recording objects, so as to produce works of art that can be viewed over and over again even though the ob- ject being photographed is in the form of performing arts. This study aims to find out how perform- ing arts are presented through the documentary technique of photography along with its analysis. The methods employed in this research were data selection and sampling techniques in choosing the photographs. The findings result in the insights that photography is able to express the artisticvisual of the performer while at the same time it improves the value of the culture because of the realistic trait embedded in photography. ABSTRAKFotografi pada awal sejarah ditemukan memiliki fungsi sebagai alat bantu melukis, dengan prototipenya yang disebut sebagai ‘camera obscura’. Kemudian fotografi terus berkembang seiring dengan munculnya penemuan baru tentang lensa, kamera, bahan kimia peka cahaya yang berkembang dari plat kaca menjadi film, dan kertas foto. Kini fotografi tidak hanya memiliki fungsi sebagai media untuk mengabadikan sebuah peristiwa, tetapi lebih ke dalam fungsi sebagai sebuah media perekam objek, sehingga menghasilkan karya seni rupa yang dapat dilihat berulang-ulang meskipun objek yang diambil gambarnya berupa seni pertunjukan. Tujuan penelitian adalah untuk mencari tahu bagaimana seni pertunjukan ditampilkan melalui teknik dokumentasi fotografi beserta pengkajiannya. Metode yang digunakan yaitu melalui seleksi data dan teknik sampling dalam memilih karya. Penemuan yang didapat dari penelitian ini adalah bahwa fotografi mampu mengungkapkan visual artistik para pelakunya dan juga dapat memberikan nilai yang lebih tinggi dalam hal kebudayaan dikarenakan sifat foto yang realis.